Sistem Pengelolahan Data Surat Masuk dan Surat Keluar Kelurahan Curug - Sri Mardiyati (Jurnal Inovasi Informatika, 2020)
An accurate and efficient application of incoming and outgoing report reports at the Curug Kelurahan Office, making an effective and efficient application of incoming and outgoing mail management in accordance with the needs of the Curug Kelurahan office, making applications that facilitate administration in mail management, making incoming mail applications and the user's outgoing mail, making an application for incoming and outgoing mail that is easily used by the user. The research method used to design this data processing application is the method of library study, observation and interviews to get more complete data. After the author designs and makes this data processing application, the writer can draw the conclusion that with this application can provide solutions in helping Curug Kelurahan in recording incoming and outgoing letters, with the application already made, the duties of the Administration and Secretary of the Village Head can be easier and better recorded because it is assisted by a computerized system. Keywords: System Design, Data Processing, Incoming and Outgoing